Shear strength evaluation of composite pavement with geotextile as reinforcement at the interface - Mohammad, Abdul Mannan; Shyue, Leong Lee; Wan Hashim, Wan Ibrahim (Elsevier Ltd., 2019)
This research was conducted to investigate the shear strength at the interface between polymer concrete and asphalt concrete with geotextile as reinforcement at the interface of these two types of concrete. The samples were tested for the parameters of different surface conditions [rough and smooth], curing types [room and thermal curing], temperature effect and the impact of geotextile as reinforcement. To investigate the correlation between these parameters, four different testing conditions were implemented. The results showed a significant improvement of shear strength for rough surface sample as compared to smooth surface sample. Moreover, samples cured in oven had lower shear strength as compared to samples cured in room condition. Besides that, high temperature has an adverse impact on the shear strength at the interface between polymer concrete and asphalt concrete due to the weakening of asphalt concrete at high temperature. As for samples reinforced with geotextile, the shear strength resistance was better as compared to unreinforced samples. Through visual observation, the types of failure under all testing conditions were mixed failure mode.